Optimizing nutritional strategies in type 2 diabetes patients receiving sodium-glucose cotransporter-2 inhibitor therapy - Shah, Aesha D.; Hebbale, Vaishnavi A.; Sarda, Prashant S.; Khobragade, Kunal J. (International Journal of Scientific Reports, 2025)
Sodium-glucose cotransporter-2 (SGLT2) inhibitors improve glycaemic control via insulin-independent glycosuria and offer cardiovascular and renal benefits. However, their safety and effectiveness are significantly influenced by dietary context, particularly in high-carbohydrate environments like India, where refined grain consumption and periodic fasting are common. This review discusses how SGLT2 inhibitor-induced energy loss, ketone production, and fluid shifts interact with regional dietary patterns. Key nutritional concerns arise in this context, including sarcopenia from caloric and protein deficits, euglycemic diabetic ketoacidosis (euDKA) triggered by carbohydrate restriction, and volume depletion due to inadequate hydration. To manage these risks, targeted nutritional strategies are essential. These include moderating carbohydrate intake (around 45-50% of total energy), maintaining sufficient protein intake (15-20% of energy), maintaining hydration (2.0-2.5 L/day), and avoiding ketogenic or overly carbohydrate restrictive diets. Furthermore, individualized dietary planning during religious fasts is important for maintaining metabolic balance. In South Asian populations, where dietary habits are deeply rooted in culture, nutrition counseling is not merely supportive but holds a central role in optimizing therapeutic outcomes with SGLT2 inhibitors.